The interplay of fungal and bacterial microbiomes on rainforest frogs following a disease outbreak - Donald T. McKnight; Roger Huerlimann; Deborah S. Bower; Lin Schwarzkopf; Ross A. Alford; Kyall R. Zenger (Ecosphere, 2022)
Abstract Emerging infectious diseases are a serious threat to wildlife populations, and there is growing evidence that host microbiomes play important roles in infection dynamics, possibly even mitigating diseases. Nevertheless, most research on this topic has focused only on bacterial microbiomes, while fungal microbiomes have been largely neglected. To help fill this gap in our knowledge, we examined both the bacterial and fungal microbiomes of four sympatric Australian frog species, which had different population‐level responses to the emergence of chytridiomycosis, a widespread disease caused by the fungal pathogen Batrachochytrium dendrobatidis (Bd). We sequenced 16,884 fungal amplicon sequence variants (ASVs) and 41,774 bacterial ASVs. Bacterial communities had higher richness and were less variable within frog species than were fungal communities. Nevertheless, both communities were correlated for both ASV richness and beta diversity (i.e., frogs with similar bacterial richness and community composition tended to also have similar fungal richness and community composition). This suggests that either one microbial community was having a large impact on the other or that they were both being driven by similar environmental factors. For both microbial taxa, we found little evidence of associations between Bd (prevalence or intensity) and either individuals' ASVs or beta diversity. However, there was mixed evidence of associations between richness (both bacterial and fungal) and Bd, with high richness potentially providing a protective effect. Surprisingly, the relative abundance of bacteria that have previously been shown to inhibit Bd was also positively associated with Bd infection intensity, suggesting that a high relative abundance of those bacteria provides poor protection against infection.